FENOMENA KOMUNIKASI KOMUNITAS PENDAKI GUNUNG(STUDI TENTANG TINDAKAN ALTRUISME PADA KOMUNITAS TAPAK KOPER DI KOTA PEKANBARU) - Asra, Bobby; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The phenomenon of altruism is not a new phenomenon in the life of society or it can be saidthat the phenomenon is actually common in the community. The phenomenon of altruism attemptspresented in this study is directed at mountain climbing communities. The purpose of this study is tofind out how the motifs, meanings, experiences, and factors of mountain climbers in PekanbaruTribal Suitcase community about the acts of altruism in mountain climbing activitiesIn this study researchers used a qualitative descriptive type, where researchers describe orconstruct in-depth interviews on the subject of research. In qualitative research, data collection isdone on natural setting, primary data source and more data collection techniques on participantobservation, in-depth interviews, and documentation.The study conducted to get the results are as follows: First, one of the conditions ofacknowledgment of altruism is the involvement of others in social interaction. Secondly, in anutshell the motive is an impulse that exists in the individual that moves or awakens so that theindividual does something. In the mountain climbing activity, the motive of altruism action itself ismore based on the sense of empathy and humanity. Thirdly, the subjective meanings of altruismacts by a mountain climber in mountain climbing activities are not merely personal experiences ofthe individual (intersubjective), but equally and together altruism acts can be done other mountainclimbers on different symptoms in interacting with others (the process). Fourth, the experience ofaltruism acts encountered or done by mountain climbers, not necessarily subjective experiencepersonally. In that sense, the experience has been shared with others and can be felt or can beexperienced by other fellow mountain climbers when confronted with certain conditions orsituations in different areas.Keywords: Social Interaction, Altruism, Community, Mountaineering